FIGURATIVE LANGUAGE IN TAYLOR SWIFT’S SONG ALBUM OF RED - Ngera, Thresia Gloria Embu; Weda, Sukardi; Nur, Riola Haya (Journal of English Literature and Linguistic Studies, 2024)
This research aims to determine the types of figurative language that appeared in "RED" album by Taylor Swift using Perrine's (1983) theory of Figurative Language. This research will also describe how the use of figurative language affects the meaning of the whole lyrics in Taylor Swift's album. Data on metaphorical language was culled from five songs on Taylor Swift's "RED" album, and analyzed using a descriptive qualitative methodology. The information was collected via a process of documenting events. The research found that there are 10 different types of figurative language, including similes, metaphors, personifications, synecdoches, metonymies, symbols, allegories, paradoxes, exaggerations, and irony. The song's lyrics don't make use of any metaphorical language, such as understatement or apostrophe. As this analysis shows, Taylor Swift often employs the rhetorical technique of simile to communicate the emotional weight of her songs' underlying themes of loss, misery, and betrayal. The purpose of this research is to identify figurative language in songs and analyze how it contributes to the songs' meanings.